.5(16n-12)=9n+11

Simple and best practice solution for .5(16n-12)=9n+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(16n-12)=9n+11 equation:


Simplifying
0.5(16n + -12) = 9n + 11

Reorder the terms:
0.5(-12 + 16n) = 9n + 11
(-12 * 0.5 + 16n * 0.5) = 9n + 11
(-6 + 8n) = 9n + 11

Reorder the terms:
-6 + 8n = 11 + 9n

Solving
-6 + 8n = 11 + 9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9n' to each side of the equation.
-6 + 8n + -9n = 11 + 9n + -9n

Combine like terms: 8n + -9n = -1n
-6 + -1n = 11 + 9n + -9n

Combine like terms: 9n + -9n = 0
-6 + -1n = 11 + 0
-6 + -1n = 11

Add '6' to each side of the equation.
-6 + 6 + -1n = 11 + 6

Combine like terms: -6 + 6 = 0
0 + -1n = 11 + 6
-1n = 11 + 6

Combine like terms: 11 + 6 = 17
-1n = 17

Divide each side by '-1'.
n = -17

Simplifying
n = -17

See similar equations:

| x^3-4x^2+6x-3=0 | | -2=x-1 | | 6x+35=-66+2.5(36x)+2 | | (14xy^2)^(1/3) | | (14xy^2)^(1/2) | | 9x^2=26x+80 | | 10000x+34000=2000x+88000 | | y=2x^3+6 | | 2x=10+11-x | | (6x-2)5=2 | | 9+20=2a+10 | | 0.25x(3.60)= | | x-3(7+2x)= | | 36x-(36/x^2)=0 | | -3(-9w+2)-9w+2(w-8)-8= | | X/2-7=7 | | 2500/y=500 | | 2x+2(5x+3)=74 | | x*2-9x=36 | | 2(5)+2(x)=40 | | 7x-3x+12=4x+6x | | 5/13 | | 2x+3-(-1+1x)=2x-2-x | | 5(3s+2m)= | | 8m-4(-5m+3)= | | (b-b^(1/3))/(b^(1/3)-1) | | y-3=-3(x+3) | | 4(x+2)-7=2x+2(-1+x) | | 11+8x-11-6x+6=11+(8x-11)-6x+6 | | 4(n-5)+15n=-4(-10n+3)-21n-8 | | 16=0 | | (x-3)x(x-5)= |

Equations solver categories